A Descriptive Analy sis o f the Translation of English Auxiliary Verbs into the Indonesian Language - Gunawan Tambunsaribu (Soshum: Jurnal Sosial dan Humaniora, 2019)
This research is a descriptive analytical research. The object of the research both the novel of “The Naked Face” and its translation “Wajah sang Pembunuh”. The purposes of this research are: a) to find out the translations of English helping verbs do/does/did into Indonesian; and b) to analyze the strategies used in translating English helping verbs do/does/did into Indonesian. In conducting this descriptive research, the researcher employed a qualitative research design with descriptive analysis. There are 30 English helping verbs which are analyzed by the researcher. The researcher analyzed the strategies used in translating English helping verbs do/does/did into Indonesian. It is found that the translator used four strategies namely emphasis on stylistic appropriateness, pragmatic, naturalizing, and syntactic strategies. Most of the strategies used are the emphasis on stylistic appropriateness. It emphasized the choice of oral mode.